Capitalism and Religious Behavior: The Case of Tumpang Pitu Gold Mining In Banyuwangi - Anang Gunaifi Alfian (Al-Albab, 2019)
In the discourse of globalization, religious agency plays an important role ranging from supporter to the opposition of the globalization. However, the understanding of globalization should involve its encounter with localities. In religious studies, religious responses can be an entry point to see how global issues impact the practice of religion. Selecting the case of the conflict over gold mine at Tumpang Pitu near Banyuwangi, East Java, as a place of conflict and encounter between capitalism and religious behavior is significant in portraying the dynamics within religious agency. Here, capitalism is discussed as the popular term among the rejecters of the mining, together with religious behavior as expression, logic, attitudes of religion. Therefore, this research is aimed to investigate the effects of gold mining project Tumpang Pitu toward religious behavior. To emphasize the study on the working of global issues and religious locality, the research employed ethnography of global connection proposed by Anna L Tsing (2005) added with religious account. The result shows that the conflict within traditionalist religious affiliation as seen in the debate over its position on the mine, a conflict extending from the grassroots to the highest level, reflects the struggle within Indonesian Islam over effective and ethical relations with global capitalism.